The landscape of implantation and placentation: deciphering the function of dynamic RNA methylation at the maternal-fetal interface - Wu, Shengyu; Xie, Han; Su, Yao; Jia, Xinrui; Mi, Yabing; Jia, Yuanhui; Ying, Hao (Frontiers in Endocrinology, 2023)
The maternal-fetal interface is defined as the interface between maternal tissue and sections of the fetus in close contact. RNA methylation modifications are the most frequent kind of RNA alterations. It is effective throughout both normal and pathological implantation and placentation during pregnancy. By influencing early embryo development, embryo implantation, endometrium receptivity, immune microenvironment, as well as some implantation and placentation-related disorders like miscarriage and preeclampsia, it is essential for the establishment of the maternal-fetal interface. Our review focuses on the role of dynamic RNA methylation at the maternal-fetal interface, which has received little attention thus far.It has given the mechanistic underpinnings for both normal and abnormal implantation and placentation and could eventually provide an entirely novel approach to treating related complications.